P09.05 Immunogenicity induced by the academic chimeric antigen receptor CAR19 (ARI-0001) in patients with CD19-positive relapsed/refractory B-cell malignancies recruited into the CART19-BE-01 clinical trial. (1st October 2020) - Klein-González, N; González-Navarro, EA; Bartoló-Ibars, A; Ortiz-Maldonado, V; Torrebadell, M; Castellà, M; Benítez, D; Caballero-Baños, M; Cabezón, R; Español, M; Baumann, T; Giné, E; et al.
Abstract : Background: Chimeric Antigen Receptor (CAR)-T cells directed against CD19 have induced high rates of response in patients with relapsed/refractory (R/R) B-cell malignancies. Two CD19-targeting constructs have been approved by the FDA and EMA (Yescarta ®, Kymriah ®) for B lymphoblastic leukemia (B-ALL) and aggressive lymphoma. Despite deep remissions, there are still major challenges and disparate data are reported about the immunogenicity induced by CART-cell therapy. On May/2017, the Spanish Agency of Medicines approved our first clinical trial (clinicaltrials.gov NCT03144583 ) with a fully academic CART-19. Materials and Methods: Eligibility criteria included R/R B-ALL (adult and pediatric), non-Hodgkin's lymphoma (NHL) and chronic lymphocytic leukemia(CLL) who failed standard therapy. The primary objective of the study was safety and secondary objectives were response rate and its duration. The humoral anti-CART response was assessed by a (cell-based) fluorescence assay to detect human anti-murine antibodies (HAMA) in patients sera. Assessment was conducted at different time points: 1) at baseline (pre-dose), 2) on day 14 after the administration of ARI-0001 cells, 3) on day 28, 4) on day 100, and 5) every 3 months thereafter. Results: Forty-seven patients (37 adults/10 pediatrics) received ARI-0001 cells. Thirty-eight patients had a diagnosis of R/R B-ALL (28 adults and 10 children); all but 5 had relapsed after allogeneic hematopoietic stem cell transplant (HCT). Seven patients had a diagnosis of NHL, four of them (57%) had relapsed after HCT, and 2 patients had a diagnosis of CLL (2). Median age was 27 years (3–68). After conditioning with fludarabine (90 mg/m2) and cyclophosphamide (900 mg/m2), a total dose of 0.5–5 x10 6 ARI-0001 cells/kg was infused. Autologous T-cells from peripheral blood were expanded and transduced with a lentivirus to express a CAR with a single-chain variable fragment (scFv) with anti-CD19 specificity, conjugated with the co-stimulatory regions 4-1BB and CD3z. The scFv was originated from a mouse monoclonal antibody A3B1. Twenty-five per cent of the patients tested positive for the presence of anti-CAR antibodies, all of them post-dose, in contrast to previous data reported on Kymriah® with a significant presence of pre-dose anti-murine CAR19 antibody. Of these 12 patients, 8 patients presented with a weak, and 4 patients with a strong presence of HAMA. The last 4 patients had lost the effectiveness of the CART- therapy at that time point, reflected by simultaneous B-cell recovery in the periphery. Moreover, three of them received a second dose of CART-19, which did not revert the relapse. Conclusions: To conclude, these data suggest the importance of the immunogenicity induced by CART-cell therapies. Immune monitoring should include the assessment of humoral response, especially before considering a second dose after relapse. Disclosure Information: N. Klein-González: None. E.A. González-Navarro: None. A. Bartoló-Ibars: None. V. Ortiz-Maldonado: None. M. Torrebadell: None. M. Castellà: None. D. Benítez: None. M. Caballero-Baños: None. R. Cabezón: None. M. Español: None. T. Baumann: None. E. Giné: None. P. Castro: None. J. Esteve: None. J. Yagüe: None. S. Rives: None. Á. Álvaro Urbano-Ispizua: None. J. Delgado: None. M. Juan: None.